A Phase I Study of Alpha‐1, 3‐Galactosyltransferase‐Expressing Allogeneic Renal Cell Carcinoma Immunotherapy in Patients with Refractory Metastatic Renal Cell Carcinoma. (6th September 2019) - Hahn, Andrew W.; Drake, Charles; Denmeade, Samuel R.; Zakharia, Yousef; Maughan, Benjamin L.; Kennedy, Eugene; Link, Charles; Vahanian, Nicholas; Hammers, Hans; Agarwal, Neeraj
Abstract: Lessons Learned: HyperAcute Renal immunotherapy was well tolerated and demonstrated antitumor activity in patients requiring salvage‐line treatment for metastatic renal cell carcinoma (mRCC). HyperAcute Renal immunotherapy was safely administered with concomitant salvage‐line treatments for mRCC, and it may be a candidate for inclusion in novel combinations for salvage treatment of mRCC because of its unique mechanism of action. Background: HyperAcute Renal (HAR) immunotherapy exploits a naturally occurring barrier to xenotransplantation and zoonotic infections in humans to immunize patients against metastatic renal cell carcinoma (mRCC) cells. HAR consists of two allogeneic renal cancer cell lines genetically modified to express α(1, 3)Gal, to which humans have an inherent pre‐existing immunity. Methods: Patients with refractory mRCC were eligible for this phase I dose‐escalation trial. Concomitant treatment was permitted after the initial 2 months of HAR monotherapy. HAR was injected intradermally weekly for 4 weeks then biweekly for 20 weeks, totaling 14 immunizations. The primary endpoint was safety and determination of a maximum tolerated dose (MTD). Results: Among 18 patients enrolled, two grade 3 adverse events (AEs) were attributed to HAR, lymphopenia and injection site reaction, and no grade 4/5 AEs occurred. The recommended phase II dose (RP2D) was 300 million cells. One patient had a partial response and eight patients had stable disease, for a disease control rate of 50% (9/18). Median overall survival with low‐dose HAR was 14.2 months and was 25.3 months with high‐dose HAR. Conclusion: In pretreated mRCC, HAR immunotherapy was well tolerated and demonstrated antitumor activity. HAR immunotherapy may be a candidate for inclusion in novel combinations for salvage treatment of mRCC.